Sculptures of Nayikas adorn the walls of Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
Inside the sanctum of the Harshnath Temple, beautiful sculptures of nayikas (female dancers) adorn the walls. Most of them are inscribed with epithets in the 10th century CE Kutila script.